The Implementation Of Hybrid Contracts For Restructuring Non-Performing Financing In Sharia Banks - Iwan Setiawan; Muhamad Izazi Nurjaman; Nana Herdiana (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
Restructuring non-performing financing is one of the solutions to save financing performance as one of the largest contributors to Islamic banking revenue. However, in practice it is not easy for Islamic banks to do so, because Islamic banks must consider the precautionary principle which has implications for risks that will occur in the future. In addition, the use of hybrid contracts in the restructuring mechanism for non-performing financing is an integral part in minimizing these risks. This study tries to reveal the application of hybrid contracts in the restructuring of non-performing financing in Islamic banking.This article uses a descriptive literature research method obtained from the results of the analysis of the primary data source, namely the substance of the legislation and the DSN-MUI fatwa. So this research uses a normative juridical approach. This type of research includes qualitative research with data analysis techniques that provide a conclusion in the form of accountable information.The results of this study reveal the fact that the application of hybrid contract contracts in the restructuring of non-performing financing in Islamic banking uses a lot of hybrid types of assembled contracts (al-'uqud al-Mujtami'ah), namely the existence of an association of contracts between tabarru' (qordh) and contracts mu'awadhat (sale and purchase, ijarah, IMBT, mudharabah and musharaka).